2019
DOI: 10.1002/adfm.201808756
|View full text |Cite
|
Sign up to set email alerts
|

Lithium–Magnesium Alloy as a Stable Anode for Lithium–Sulfur Battery

Abstract: Lithium-sulfur (Li-S) batteries are regarded as the promising next-generation energy storage device due to the high theoretical energy density and low cost. However, the practical application of Li-S batteries is still limited owing to the cycle stability of both the sulfur cathode and lithium anode. In particular, the instability in the bulk and at the surface of the lithium anode during cycling becomes a huge obstacle for the practical application of Li-S battery. Herein, a Li-rich lithium-magnesium (Li-Mg) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
128
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 184 publications
(135 citation statements)
references
References 56 publications
0
128
0
Order By: Relevance
“…Additionally, there are literature reports that suggest a very high lithium diffusion coefficient of the β-phase of up to D(Li) ≈ 10 −7 cm² s −1 , which is the key ingredient to the better transport kinetics inside the alloy anode. [48] In solid-state batteries, the retained structural rigidity and morphological stability will have an even greater influence, as morphologically unstable anodes (such as pure lithium anodes) can hardly operate without high external pressure. Even if the lithium in a remaining α-phase cannot be addressed during cycling, the values are as high as 1850 mAh g −1 and 1220 mAh cm −3 , which are still much higher compared to commonly used graphite anodes (350 mAh g −1 and 760 mAh cm − ³).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, there are literature reports that suggest a very high lithium diffusion coefficient of the β-phase of up to D(Li) ≈ 10 −7 cm² s −1 , which is the key ingredient to the better transport kinetics inside the alloy anode. [48] In solid-state batteries, the retained structural rigidity and morphological stability will have an even greater influence, as morphologically unstable anodes (such as pure lithium anodes) can hardly operate without high external pressure. Even if the lithium in a remaining α-phase cannot be addressed during cycling, the values are as high as 1850 mAh g −1 and 1220 mAh cm −3 , which are still much higher compared to commonly used graphite anodes (350 mAh g −1 and 760 mAh cm − ³).…”
Section: Introductionmentioning
confidence: 99%
“…[185][186][187] Kong's research group suggested that a Li-rich lithium-magnesium (LiÀ Mg) alloy forms a MgO-containing passivation layer on a LiÀ Mg alloy surface during reaction with lithium in the cell. [188] The study was based on the difference in exchange current density between Mg (0.81 mA cm À 2 ) and Li Figure 6. a) Schematic illustration of the ability of a LiPON-coated lithium metal anode in the lithium-sulfur battery.…”
Section: Controlling the Lithium Metal Surface: Chemical Components Amentioning
confidence: 99%
“…> 500 (1600 mA g À 1 ) TMP-HFE [184] Electrolyte-additive in situ 1 350 S@pPAN composite (5.6 mg cm À 2 ) > 50 (0.483 mA cm À 2 ) LiPON [179] Nitrogen plasma-assisted deposition ex situ 3 600 CNT/S composite (7 mg cm À 2 ) 120 (0.79 mA cm À 2 ) MgO-containing layer [188] Reaction of LiÀ Mg alloy in situ --NBC/CNT/C (2 mg cm À 2 ) 200 (168 mA g À 1 ) N-doped porous carbon nanosheet [192] Attaching the Li surface ex situ 0.5 1600 N-CNT/S (0.7 mg cm À 2 ) 1400 (3.0 A g À 1 ) Metal fluoride complex [193] (MFC, Li 18-crown-6/PVDF [261] Spin coating ex situ 1 149 S 200 (335 mA g À 1 ) Sericin protein [262] Drop casting ex situ 10 160 N-doped carbon/S (1 mg cm À 2 ) 520 (1672 mA g À 1 ) Fluorinated ethers [170] Electrolyte-additive in situ --Bulk sulfur 200 (167 mA g À 1 ) Li 3 PS 4 [169] Immersing Li in P 4 S 16 / NMP ex situ 0.5 2000 S@C (0.8-1.3 mg cm À 2 ) 400 (5 A g À 1 ) Li metal PEO-UPy/THF [263] Drop casting ex situ 1 1000 NMC622 (8 mg cm À 2 ) 200 (180 mA g À 1 ) Toluene (TOL) [203] Electrolyte-additive in situ --NMC532 (9 mg cm À 2 )…”
mentioning
confidence: 99%
“…The Mg matrix provided host for the lithium to acquire an even deposition. Also, Mg element participated in the formation of a robust SEI (Kong et al, 2019). Other types of lithium alloys such as Li/Sn (Qiu et al, 2019) and Li/Al (Zhong et al, 2018) had also been proven effective though more studies are still needed.…”
Section: Providing Host Materials For Lithium Depositionmentioning
confidence: 99%